WANITA dalam Qur an Muhammad Muttawali Syarawi ; penerjemah, Abu Abdillah almansur ; penyunting, Jamilah ; ilustrasi, Edo Abdullah - Syarawi, Muhammad Muttawali; Almansur, Abu Abdillah; Jamilah; Abdullah, Edo (Gema Insani Press, 1995)
45 hlm. ; 17 cm.